In silico analysis of quercetin and its derivatives as potential TRPC6-targeted treatments for diabetic neuropathy - Pangestu, Maryo Adjie; Auli, Winni Nur; Saputro, Anjar Hermadi; Pasaribu, Romualdo; Maharani, Gita Putri; Yunita, Nadia Rahma; Choiriah, Ika Putri; Ainun, Hadhistia Nur; Erniningsih, Ni Ketut; Andini, Citra (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: Diabetic neuropathy is a condition that arises as a complication of diabetes mellitus and often causes pain in patient. Quercetin and its derivatives have antinociceptive activity, making them potential agents for relieving the pain associated with diabetic neuropathy. Objective: This study aims to analyze the interactions between quercetin and its eight derivatives with canonical transient receptor potential channels 6 (TRPC6) as protein target. Method: The TRPC6 structure (PDB ID: 6UZ8) was prepared and validated with redocked to native ligand R0D using Autodock 4.2.6, with the established grid box and grid center settings. The test compounds were then optimized and docked using the same grid box and grid center settings as in the validation process, followed by visualization and analysis of the docking results. Results: The compound with the best affinity for TRPC6 was tamarixetin, with a binding energy value of -3.27 kcal/mol, close to the binding energy value of the native ligand, which was -4.22 kcal/mol. The amino acid residues interacting with tamarixetin at the active site were 702-Asn, 705-Tyr, 706-Val, and 709-Gly. This indicates that tamarixetin and the native ligand bind to the same active site amino acids, resulting in a similar affinity to the native ligand in inhibiting TRPC6. Conclusion: A total of eight quercetin derivatives were predicted to have TRPC6 antagonistic activity against diabetic neuropathy, with tamarixetin exhibiting the highest affinity compared to the other quercetin derivatives.